Analisis Minat Siswa Sekolah Dasar terhadap Ekstrakurikuler Renang Ditinjau dari Faktor Eksternal - Stania, Valia; Prakoso, Bayu Budi; Hartoto, Setiyo; Khory, Fifukha Dwi (MAN Insan Cendekia Jambi, 2025)
This study aims to investigate the level of interest of 3rd and 4th grade students at Muhammadiyah 4 Elementary School Surabaya in participating in swimming extracurricular activities, analyze differences in interest based on gender, and examine the role of parental support, peers, facilities, and coaches in shaping student interest. The type of research used is non-experimental research with a quantitative descriptive method. The sampling technique used was total sampling, while data analysis used SPSS software with quantitative descriptive methods, Likert scale, t-test, linear regression, ANOVA, and post-hoc test. The study's results indicate a very high (60%) level of student interest. This interest was significantly influenced (p < 0.05) by parental support, peers, availability of facilities, and the role of coaches, with the coach factor being the most dominant. Additionally, the study revealed a difference in interest between male and female students, with female students demonstrating a higher level of interest than male students. Thus, it can be concluded that effective swimming extracurricular coaching cannot rely solely on students' intrinsic interest but is also influenced by extrinsic support that can create a positive, inclusive, and enjoyable learning environment for all students.